2017
DOI: 10.1182/bloodadvances.2017005231
|View full text |Cite
|
Sign up to set email alerts
|

Associations of α-thalassemia and BCL11A with stroke in Nigerian, United States, and United Kingdom sickle cell anemia cohorts

Abstract: Alpha-thalassemia and the BCL11A rs1427407 T allele are commonly observed in sickle cell anemia (SCA) patients and are associated with reduced hemolysis and higher hemoglobin F levels, respectively. We investigated whether a high-risk genetic profile, defined as SCA patients who did not inherit either α-thalassemia or the BCL11A rs1427407 T allele, had stronger associations with clinical and laboratory variables than the individual genetic components in the University of Ibadan cohort (n=249). We then replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
7
14
0
Order By: Relevance
“…The two α‐globin genes on chromosome 16 are located within a 4‐kb duplicated region leading to the possibility of rearrangements including deletions and triplications with many attendant downstream consequences . The present study confirmed earlier reports that the 3.7 κb α‐globin gene deletion is the common α‐thal allele among Africans as none of the participants had the 4.2Kb α‐globin gene deletion.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The two α‐globin genes on chromosome 16 are located within a 4‐kb duplicated region leading to the possibility of rearrangements including deletions and triplications with many attendant downstream consequences . The present study confirmed earlier reports that the 3.7 κb α‐globin gene deletion is the common α‐thal allele among Africans as none of the participants had the 4.2Kb α‐globin gene deletion.…”
Section: Discussionsupporting
confidence: 90%
“…The observed hematological profile of patients with α‐thal in this study has been previously described . The increased Hb and red blood cell count are due to the decrease in the intracellular concentration of HbS, and number of dense red blood cells .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…5 Similarly, co-inheritance of α-thalassemia is protective against some SCD-related complications, such as hemolysis, stroke, and kidney disease. 6,7 Availability of appropriate comprehensive medical care for SCD that combines newborn screening, penicillin prophylaxis, screening for stroke risk, transfusion program, and the use of hydroxyurea, in high income countries, usually mitigates morbidity and facilitates longer survival of SCD patients. 8 This is, however, not the case in most of SSA, due to the combined effect of inappropriate care and often severe clinical complications, 7,9 compounded by other factors such as malaria, malnutrition, infectious diseases of childhood, and poverty.…”
Section: Introductionmentioning
confidence: 99%